Intravascular Lithotripsy-Assisted Transfemoral TAVI: The Copenhagen Experience and Literature Review - Sawaya, Fadi J.; Bajoras, Vilhelmas; Vanhaverbeke, Maarten; Wang, Christina; Bieliauskas, Gintautas; Søndergaard, Lars; De Backer, Ole (Frontiers in Cardiovascular Medicine, 2021)
Transcatheter aortic valve implantation (TAVI) is currently an established therapy for elderly patients with symptomatic severe aortic valve stenosis across all surgical risk categories. Access is an important aspect when planning for and performing TAVI. The superiority of a transfemoral (TF) approach compared to a transthoracic (transapical, direct aortic) approach has been demonstrated in several studies. Recently, the introduction of intravascular lithotripsy (IVL) has made it possible to treat patients with calcified iliofemoral disease by TF approach. This article aimed to provide a comprehensive overview on the following aspects: (1) preprocedural planning for IVL-assisted TF-TAVI; (2) procedural aspects in IVL-assisted TF-TAVI; (3) outcomes of IVL-assisted TF-TAVI in an experienced TAVI centre; and (4) literature review and discussion of this new emerging approach.